2007
DOI: 10.1364/ao.46.007652
|View full text |Cite
|
Sign up to set email alerts
|

Digital holographic particle validation via complex wave

Abstract: The inability to distinguish between particle images and noise in holographic reconstruction of dense particle fields hampers the advancement of holographic particle diagnostic techniques including holographic particle image velocimetry. We developed a method to separate particles from the noise by unlocking a unique particle signature in the complex reconstructed field. This complex-wave signature is present in digital particle holograms recorded at any scattering angle. Simulations of single and multiple par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Note that a darker cone extends out beyond the point object, so that points near to the object have minimum intensities at defocus greater than zero, and thresholding is necessary to limit the focus metric to the correct region. [89], [274]. Each of these methods is developed for use with particles.…”
Section: Domínguez-caballero Deviated From the Norm And Searched Instmentioning
confidence: 99%
See 3 more Smart Citations
“…Note that a darker cone extends out beyond the point object, so that points near to the object have minimum intensities at defocus greater than zero, and thresholding is necessary to limit the focus metric to the correct region. [89], [274]. Each of these methods is developed for use with particles.…”
Section: Domínguez-caballero Deviated From the Norm And Searched Instmentioning
confidence: 99%
“…(Note that particle metrics such as de Jong's complex signature [89] or Pan's minimum imaginary component variance [274] are inappropriate for these cases since the object cannot be considered to be point-like.) The assumption of minimum intensity is valid when the particles go out of focus quickly and the noise level is low, so that noise does not signi…cantly impact the intensity and the object edges have a low value for only a few reconstruction slices.…”
Section: Detection Using Focus Metricsmentioning
confidence: 99%
See 2 more Smart Citations
“…A metric is therefore most commonly applied to determine the axial position. Reported metrics have been based on intensity [2], intensity gradients [3] or a combination of both [4], complex metrics have also been reported [5,6]. We have in a previous paper showed that the axial particle position can be found by tracking the wavefront curvature [7].…”
Section: Introductionmentioning
confidence: 99%